Pengungkapan Manajemen Risiko, Modal Intelektual dan Good Corporate Governance pada Nilai Perusahaan - Rizki Ramadhani; Damayanti, Esti; Gustinya, Diana (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2026)
This study aims to analyze the effect of risk management disclosure, intellectual capital, and good corporate governance on firm value in manufacturing companies within the consumer goods industry subsector listed on the Indonesia Stock Exchange during the 2020–2024 period. The research sample was obtained using a purposive sampling method, resulting in a total of 100 observational data points. The data used are secondary data derived from the companies’ annual reports. Data analysis was conducted using panel data regression through the EViews 12 software. The results indicate that risk management disclosure and several components of intellectual capital have a significant effect on firm value. Meanwhile, the implementation of good corporate governance shows varying results in relation to firm value. These findings suggest that information transparency, the management of intangible assets, and corporate governance play important roles in enhancing investor confidence and firm value.